"Men are always scared to test with their partners … it is like taking them to the Police": Motivations for and barriers to couples' HIV counselling and testing in Rakai, Uganda: a qualitative study. Issue 2 (18th September 2014) - Matovu, Joseph KB; Wanyenze, Rhoda K; Wabwire‐Mangen, Fred; Nakubulwa, Rosette; Sekamwa, Richard; Masika, Annet; Todd, Jim; Serwadda, David
Abstract : Introduction: Uptake of couples' HIV counselling and testing (couples' HCT) can positively influence sexual risk behaviours and improve linkage to HIV care among HIV‐positive couples. However, less than 30% of married couples have ever tested for HIV together with their partners. We explored the motivations for and barriers to couples' HCT among married couples in Rakai, Uganda. Methods: This was a qualitative study conducted among married individuals and selected key informants between August and October 2013. Married individuals were categorized by prior HCT status as: 1) both partners never tested; 2) only one or both partners ever tested separately; and 3) both partners ever tested together. Data were collected on the motivations for and barriers to couples' HCT, decision‐making processes from tested couples and suggestions for improving couples' HCT uptake. Eighteen focus group discussions with married individuals, nine key informant interviews with selected key informants and six in‐depth interviews with married individuals that had ever tested together were conducted. All interviews were audio‐recorded, translated and transcribed verbatim and analyzed using Nvivo (version 9), following a thematic framework approach. Results: Motivations for couples' HCT included the need to know each other's HIV status, to get a treatment companion or seek HIV treatment together – if one or both partners were HIV‐positive – and to reduce mistrust between partners. Barriers to couples' HCT included fears of the negative consequences associated with couples' HCT (e.g. fear of marital dissolution), mistrust between partners and conflicting work schedules. Couples' HCT was negotiated through a process that started off with one of the partners testing alone initially and then convincing the other partner to test together. Suggestions for improving couples' HCT uptake included the need for couple‐ and male‐partner‐specific sensitization, and the use of testimonies from tested couples. Conclusions: Couples' HCT is largely driven by individual and relationship‐based factors while fear of the negative consequences associated with couples' HCT appears to be the main barrier to couples' HCT uptake in this setting. Interventions to increase the uptake of couples' HCT should build on the motivations for couples' HCT while dealing with the negative consequences associated with couples' HCT.